The effect of dietary pumpkin seed cake and extruded linseed on blood haemato-chemicals and milk quality in Alpine goats during early lactation - Klir, Željka (Array, 2020)
Due to the high content of crude protein and high concentration of unsaturated fatty acids, pumpkin seed cake (PSC) could be a good quality feedstuff for ruminants, while extruded linseed (ELS) has already shown some beneficial effect on fatty acids proportion of goat milk. Besides, lactation is the most demanding period when monitoring the metabolic condition of animal. Therefore, the aim of this study was to determine the effect of PSC and ELS replacing soybean meal in diets of dairy goats on blood haemato-chemical parameters and milk quality. A 28 lactating French Alpine dairy goats were monitored within 20 days in early lactation. Diet of each groups had a balanced content of energy and crude protein, and a slight difference in lipid content. Goats in control group (n = 9) received soybean meal and extruded soybean. In experimental groups soybean was partially replaced with ELS (n = 10) or completely with PSC (n = 9). Dietary treatments had no effect on haemato-chemical parameters, although PSC increased concentration of globulins in serum. PSC lowered linoleic acid compared to control. ELS increased proportion of α-linolenic acid, eicosapentaenoic acid, and total n-3 fatty acids in milk. Positive correlations were found between non-esterified fatty acids (NEFA) and ratio C18:1/C15:0, NEFA and ratio C17:0/C15:0, as well as β-hydroxybutyrate and ratio C17:0/C15:0. The replacement of soybean meal with PSC or partially with ELS is feasible with respect to haemato-chemical parameters of early lactating dairy goats, while ELS had much beneficial effect on fatty acids  compared to PSC.